2021
DOI: 10.1002/jcop.22566
|View full text |Cite
|
Sign up to set email alerts
|

The Inspired Life Program: Development of a multicomponent positive psychology intervention for rural adults in Ghana

Abstract: Although several theories and studies have explored human strengths and mental well-being at the global level, these insights are rarely tested and translated into practice in sub-Saharan Africa. This study aims to describe the development of a 10-session multicomponent positive psychology intervention, the Inspired Life Program (ILP), designed to promote mental health and reduce symptoms of depression and negative affect in rural adults in Ghana. Guided by the Medical Research Council's framework for developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…As a result of the 10-session intervention which reported medium to large effect sizes for MHC domains, 77.5% of the participants in the intervention group were flourishing compared to 38.1% for the control group at the 3-month follow-up, showing that the gains in the primary outcome of positive mental health were maintained in the period after the intervention. Although the control group was conditioned as an assessment only group rather than treatment as usual, the community-based participatory research approach to the development and administration of the ILP showed many indicators of implementation success marked by clear effect sizes, practical relevance, and guidance for practitioners ( Appiah et al, 2021a ). As these studies utilizing the MHC in Ghana focused on known groups and communities, they made efforts to maximize demographic representativeness in their study designs; however, their focus was not on youthful populations and reported chiefly on established and elderly adults.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the 10-session intervention which reported medium to large effect sizes for MHC domains, 77.5% of the participants in the intervention group were flourishing compared to 38.1% for the control group at the 3-month follow-up, showing that the gains in the primary outcome of positive mental health were maintained in the period after the intervention. Although the control group was conditioned as an assessment only group rather than treatment as usual, the community-based participatory research approach to the development and administration of the ILP showed many indicators of implementation success marked by clear effect sizes, practical relevance, and guidance for practitioners ( Appiah et al, 2021a ). As these studies utilizing the MHC in Ghana focused on known groups and communities, they made efforts to maximize demographic representativeness in their study designs; however, their focus was not on youthful populations and reported chiefly on established and elderly adults.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PPIS that were based on behavioural or acceptance and commitment therapy, as well as reminiscence interventions, were particularly effective [16]. Unlike traditional psychological interventions that target only clinical populations, PPIs can be effectively employed across various populations and have been used in education [17], organisations [18], clinical populations [4,5], healthy populations [19], local communities [20], and at-risk groups [21]. Thus, a key strength of PPIs is their breadth and flexibility.…”
Section: Positive Psychology Interventions: Purpose Examples and Evid...mentioning
confidence: 99%
“…It is also possible to target social support through PPIs. For example, Appiah and colleagues [20] developed a PPI program for adults in rural Ghana that aimed to build peer support, psychosocial skills, and collaborative therapeutic relationships. Participants of the intervention reported an increased sense of positivity and well-being, along with stronger social networks and relationships.…”
Section: The Role Of Peer and Social Support In Ppismentioning
confidence: 99%
“…We posit that what is needed is a broader conceptualisation of an IC process that allows researchers to manage ethico-cultural conflicts with the IC more appropriately in their research settings, in circumstances when UEGs are silent or take a contrary stance. We contend that within a multi-stakeholder approach comprising local communities, Universities, research institutions, IRBs, and research-based NGOs, it should be possible to build on existing knowledge [31][32][33][34], and on recent community-based research efforts in Ghana [1,40,[46][47][48] to develop a framework that reflects and takes into account the general perspective and cultural norms of the Ghanaian peoples, as well as the principles of the UEGs.…”
Section: The Declaration Of Helsinki and Its Implications For Social Science Researchmentioning
confidence: 99%
“…Although we do not question the principle of individual autonomy or the need for vigorous IC policy, we argue that the IC process for research participants should provide participants with adequate information about the study in a language and at the level of their understanding, and should also contribute to minimising the incidence of deception and coercion. Our view is informed by research and field observations [3,5,25,40,[46][47][48], and by Kant's [49] conceptualisation of autonomy as a medium by which individuals freely exercise their practical reasoning, which also provides them the forum to safeguard and protect themselves against coercion and deception. The IC process and its documentation, as well as guidelines for the conduct of social science research in the more communal sub-Saharan African context, should go beyond ensuring the autonomy and decisional authority of prospective participants, to also include mechanisms to prevent deception and coercion.…”
Section: The Declaration Of Helsinki and Its Implications For Social Science Researchmentioning
confidence: 99%